Karbon Aktif Kulit Bawang Merah (Allium ascalonicum) untuk Mereduksi Bilangan Asam dan Peroksida: Indonesia - Lubis, Ridwan Yusuf; Insani, Rizki; Husnah, Miftahul; Silalahi, Ali Affan (Teknik Lingkungan Universitas Islam Indonesia, 2026)
Activated carbon is one of the adsorption materials commonly used to improve the quality of used cooking oil. This study aims to determine the effect of varying concentrations of phosphoric acid (H₃PO₄) as a chemical activator on activated carbon derived from red onion peel. The research data were expressed quantitatively through physical and chemical characterization, while the results of color and odor tests were presented descriptively. Activated carbon from red onion peel was successfully produced through physical activation (400 °C) and chemical activation (H₃PO₄) with concentration variations A (8%), B (12%), C (16%), and D (20%). The characterization results showed a decrease in moisture content, ash content, and volatile matter content, while the carbon content increased. Sample D met the requirements of SNI 06-3730-1995 for all physical and chemical characteristics. An increase in adsorption ability for acid value was observed in line with the increase in activator concentration. The ability to reduce peroxide value decreased in samples C and D compared to sample B, but still met the SNI 3741:2013 standard. The most optimal characterization and adsorption performance were obtained in sample D, with an acid value of 0.33% (mg KOH/kg) and a peroxide value of 8 (meq O₂/kg).